Relatório da sustentabilidade na Europa: diferenças em termos de legislação e valorização (Revista Lusófona de Economia e Gestão das Organizações, 2017)
Over the past few years, the number of socially responsible companies has been increasing significantly throughout the world and predominantly in Europe. This trend has accelerated the need to provide credibility, and also to create legislation that supports the information provided. As a result, the Global Reporting Initiative (GRI) was created with the aim of helping organisations to provide information about sustainability, as well as to assist stakeholders in interpreting it. However, the publication of social responsibility reports represents an additional cost and effort for the companies since it is necessary to provide extra resources and, for this reason, not all companies adopt this measure. Moreover, social responsibility can be a mandatory or voluntary requirement, depending on the country and the rules imposed by the government where the companies operate. In this context, the aim of this study is two-fold. Firstly, we provide a deep analysis about the evolution as well as the similarities and differencesamong European countries in terms of sustainability reporting over the 2001-2013 period following the GRI criteria. Secondly, we provide evidence about the value relevance of this practice for European firms.